PENGARUH MINAT BELAJAR, KEPERCAYAAN DIRI, DISIPLIN BELAJAR, LINGKUNGAN SEKOLAH DANBULLYING TERHADAP PERILAKU BELAJAR KELOMPOK KELAS VIIDI SMP N 6 KOTA SOLOK - Vini Aryulia (Horizon, 2021)
This study aims to analyze: 1) the effect of partial interest in learning on group learning behavior, 2) the effect of partial self-confidence on group learning behavior, 3) the effect of partial learning discipline on group learning behavior, 4) the effect of partially school environment on behavior group learning, 5) the effect of bullying partially on group learning behavior and 6) the influence of learning interest, self-confidence, learning discipline, school environment and bullying simultaneously on group learning behavior. The results of the study are first, interest in learning greatly influences group learning behavior. Both self-confidence are very influential on group learning behavior. The three learning disciplines are very influential on group learning behavior. The four school environments affect group learning behavior. Fifth, bullying is very influential on group learning behavior. The six learning interests, self-confidence, learning discipline, school environment and bullying affect group learning behavior.